Need-Based Evangelism as a Tool for Economic Empowerment and Poverty Alleviation in Nigerian Pentecostal Churches (British Journal of Multidisciplinary and Advanced Studies, 2024)
Pentecostal churches in Nigeria face the dual challenge of addressing both spiritual and socio-economic needs. This study explores the role of need-based evangelism as a tool for economic empowerment and poverty alleviation, focusing on how Pentecostal churches can integrate spiritual and practical support for wholistic community development. Using descriptive, qualitative, and quantitative research methodologies, data was collected from diverse age groups within Pentecostal congregations and their financial supporters. Findings reveal significant needs for education, vocational training, and employment opportunities, particularly among young adults. Middle-aged and older adults provide critical financial support, expertise, mentorship, and advisory roles, while younger members contribute through volunteerism and innovative ideas. The study recommends comprehensive vocational training, enhanced financial support, community engagement, and continuous evaluation to ensure sustainable impact. These measures aim to empower both younger and older demographics and strengthen the role of need-based evangelism in economic empowerment and poverty alleviation within Nigerian Pentecostal churches.